2020
DOI: 10.1590/1980-5373-mr-2020-0269
|View full text |Cite
|
Sign up to set email alerts
|

Response of a DIN 18MnCrSiMo6-4 Continuous Cooling Bainitic Steel to Different Plasma Nitriding Gas Mixtures

Abstract: Continuous cooling bainitic steels has been widely used in industrial processes owing to its excellent mechanical properties and toughness. Although the surface properties of them are acceptable for many purposes, for their use in mechanical components like gears, it is necessary to improve their surface properties. Plasma nitriding treatments was carried out of a DIN 18MnCrSiMo6-4 steel at 500 °C, with three different nitrogen gas composition: 76, 24 and 5 vol.% nitrogen in hydrogen, for 3, 6 and 9 hours. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 21 publications
(52 reference statements)
3
16
0
Order By: Relevance
“…Similarly, when the drop in hardness was gradual, the reduction in compressive residual stresses was gradual. It is also noteworthy that the residual stresses profiles become tensile in the vicinity of the case/core interface, as already observed by other researchers 18,22,23,36,37 . Compressive residual stresses found in the diffusion zone are the result of structural misfits caused by the precipitation of alloy nitrides and carbonitrides in the iron matrix 17 , and also due to the saturation of the iron network with interstitial nitrogen.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Similarly, when the drop in hardness was gradual, the reduction in compressive residual stresses was gradual. It is also noteworthy that the residual stresses profiles become tensile in the vicinity of the case/core interface, as already observed by other researchers 18,22,23,36,37 . Compressive residual stresses found in the diffusion zone are the result of structural misfits caused by the precipitation of alloy nitrides and carbonitrides in the iron matrix 17 , and also due to the saturation of the iron network with interstitial nitrogen.…”
Section: Resultssupporting
confidence: 83%
“…All the plasma nitrided samples showed diffraction peaks that indicate the formation of a compound layer 22,23 . Figures 3a-c also show the formation of a biphasic compound layer (ε-Fe 2-3 (C)N and γ'-Fe 4 N) on the plasma nitrided samples with 24 and 76 vol.% N 2 , while the plasma nitrided samples with 5 vol.% N 2 indicated a monophasic compound layer (γ'-Fe 4 N).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma nitriding leads to an increase in hardness on the surface (Table 2), for the reason it also ends up creating a less ductile region more prone to brittle fracture 36 . The mechanical properties of the diffusion zone influence the fracture properties of the compound layer, since the diffusion zone provides support for the surface compound layer 15,16,36 . Previous work 15 showed that the higher nitriding temperature and time promoted an increase in the fracture toughness of the compound layer.…”
Section: Microstructure Phase Analysis and Microhardnessmentioning
confidence: 99%
“…The plasma nitriding process can be used to develop outstanding surface properties while carrying treatments using relatively low treatment temperatures 15,16 , thus representing a reliable alternative to conventional thermal and thermochemical treatments. Since long nitriding times can have a detrimental effect on the mechanical properties of steel, the treatment temperature should be carefully selected to avoid overheating of the steel itself and to preserve the bainitic microstructure of these steels, as well as softening of the plasma nitrided layer due to the excess aging of nitrides 15,17 .…”
Section: Introductionmentioning
confidence: 99%